The Effect Of Aluminum Content On Properties Of TiAI Based Binary Alloys. - Manalu, Okti J. P.; Astrawinata, Rizal; Mohd. Sharif, Nurulakmal; Basuki, Eddy A.; Maruyama, Toshio (2005)

(untitled)
Four alloys in Ti-AI binary system (Ti-50AI, Ti-53AI, Ti-60AI and Ti-65AI in at.%) have been produced by orc-Inclting process in a specially-designed and locally made furnace . The alloy samples were then oxidized in air a! 900°C 50 hours inside a muffle furnace. In this study microstructures and phases of the alloys have been characterized using XRD and SEM/EDS to link on their properties.